Tiktok Micro Influencer as a New Communication Marketing Tactic in Building Brand Equity - Putu Dea Anggita Yanti; Muhamad Sulhan (Universitas Pendidikan Ganesha, 2023)
Marketing influencer is a recent phenomenon occurs due to the marketing era 4.0. This study aimed at elaborating Tiktok micro influencer as a communication tactic in marketing field to build brand equity at WYAH Art & Creative Space Ubud. Qualitative method was used as a research design particularly by adapting case study model. The subjects were one Tiktok micro influencer, 2 visitors, and 2 marketing staffs of WYAH Art & Creative Space Ubud. The data were collected by conducting observation, interview, and document analysis through the use of observation sheet and interview guide. The collected data was analysed quantitatively by using Qualitative Data Analysis. The findings showed that TikTok micro influencer could be used as an opinion leader in marketing communications. The vibes of normal people shown by the Tiktok micro influencer delivered the message naturally. Marketing communication tactics with TikTok micro influencer could be used free of charge to communicate and build a brand equity for WYAH Ubud through creating awareness in all components of TikTok micro influencer. They could communicate the brand image of WYAH Ubud and create high awareness among TikTok users. Continuously, this tactic built a strong brand equity for its brands, including WYAH Ubud.